# Number-theoretic transform

The number-theoretic transform is similar to the discrete Fourier transform, but operates with modular arithmetic instead of complex numbers.

The discrete Fourier transform is given by

The number-theoretic transform operates on a sequence of n numbers, modulus a prime number p of the form p=ξn+1, where ξ can be any positive integer.

The number [itex]e^{-\frac{2\pi i}{n}}[itex] is substituted with a number ωξ where ω is a "primitive root" of p, a number where the lowest positive integer ж where ωж=1 is ж=p-1. There should be plenty of ω which fit this condition. Note that both [itex]e^{-\frac{2\pi i}{n}}[itex] and ωξ raised to the power of n are equal to 1 (mod p), all lesser positive powers not equal to 1.

The number-theoretic transform is then given by

The inverse number-theoretic transform is given by

Note that ωp-1-ξ=ω-ξ, the reciprocal of ωξ, and np-2=n-1, the reciprocal of n. (mod p)

The inverse works because [itex]\sum_{k=0}^{n-1}z^k[itex] is n for z=1 and 0 for all other z where zn=1. A proof of this (should work for any division algebra) is

[itex]z\left(\sum_{k=0}^{n-1}z^k\right)+1=\sum_{k=0}^nz^k[itex]
[itex]z\sum_{k=0}^{n-1}z^k=\sum_{k=0}^{n-1}z^k[itex] (subtracting zn=1)
[itex]z=1\ \mathrm{if}\ \sum_{k=0}^{n-1}z^k\ne 0[itex] (dividing both sides)

If z=1 then we could trivially see that [itex]\sum_{k=0}^{n-1}z^k=\sum_{k=0}^{n-1}1=n[itex]. If z≠1 then the right side must be false to avoid a contradiction.

It is now straightforward to complete the proof. We take the putative inverse transform of the transform.

[itex]f^{-1}(f(x))_h=n^{p-2}\sum_{j=0}^{n-1}\left(\sum_{k=0}^{n-1}x_k\left(\omega^\xi\right)^{jk}\right)(\omega^{p-1-\xi})^{hj}\mod p[itex]
[itex]f^{-1}(f(x))_h=n^{p-2}\sum_{j=0}^{n-1}\sum_{k=0}^{n-1}x_k(\omega^\xi)^{jk-hj}\mod p[itex]
[itex]f^{-1}(f(x))_h=n^{p-2}\sum_{k=0}^{n-1}x_k\sum_{j=0}^{n-1}(\omega^{\xi(k-h)})^j\mod p[itex]
[itex]f^{-1}(f(x))_h=n^{p-2}\sum_{k=0}^{n-1}x_k\left\{\begin{matrix}n,&k=h\\0,&k\ne h\end{matrix}\right\}\mod p[itex] (since ωξn=1)
[itex]f^{-1}(f(x))_h=n^{p-2}x_hn\mod p[itex]
[itex]f^{-1}(f(x))_h=x_h\mod p[itex]

• Art and Cultures
• Countries of the World (http://www.academickids.com/encyclopedia/index.php/Countries)
• Space and Astronomy